The Human qualities needed to complete the global eradication of polio - Maher, Dermot (2013)
Argues that the total eradication of polio depends on the less tangible but equally important human qualities of energy, realism, articulacy, determination, imagination, collaboration, adaptability, tactical awareness, innovation, openness and nimbleness (acronym ERADICATION). Adds that by paying attention to these human qualities, the stakeholders involved may be more likely to achieve global polio eradication.